Resposta à Intervenção como Estratégia Diagnóstica para Dislexia - Medda, Mariana Gobbo [UNIFESP] (2020)
Objective: The purpose of this study was to develop and apply a diagnostic process for dyslexia based on the Response to Intervention (RTI) model for children in Elementary School I. At first, the specific goal was to identify the pattern of changes in the participants performance after intervention in tasks concerning phonological awareness, working memory, lexical access, reading and writing skills. Subsequently, we analyzed which functions had a significant effect for differentiating participants with a profile for dyslexia and a profile of learning difficulties. Methods: The sample consisted of 30 participants at risk for dyslexia, aged 8-11, both sexes, from public or private schools in São Paulo, from 3rd to 5th grade. All of them were subjected to a battery of cognitive as well as reading and writing tests, before and after 12 cognitivelinguistic skills stimulation sessions. In order to monitor performance decoding skills and reading speed were also assessed throughout the intervention, at five different times, by reading and writing lists of words and pseudowords. For statistical analysis of comparison of each variable before and after intervention as well as for comparison of monitoring variables, a mixed model of repeated measures (GMM) was conducted. Qualitative and quantitative analyses of the differences in test performances among participants were used to understand the profiles of dyslexic versus non dyslexic groups (GLzM test). Results: There were statistically significant changes in the following functions: phonological awareness, rapid automatized naming, narrative and expository texts reading speed , narrative text comprehension, rate of correct answers and errors, as well as typology of errors in reading and writing words and pseudowords. Among these functions, the ones that showed the greatest differentiating effect between the two groups were: phonological awareness, expository text reading speed, error rates and error types in reading and writing. It was observed that the dyslexic group presented less gain in all functions after the intervention. Conclusions: Intervention focused on the stimulation of phonological skills added to explicit and systematic teaching of graphophonemic correspondence contributed positively to the evolution of the group participants. Phonological skills, mainly those related to phonological awareness, the ability to manipulate and discriminate sounds as well as their graphemic correspondences were particularly important for the understanding of learning difficulties. The results of this study suggest that the profile of dyslexia is associated with oscillating or stable learning curves, that is, a performance with minor changes regarding linguistic skills and decoding errors. We support that the Response to Intervention Model (RTI) comprises a more valid alternative for the identification of children with dyslexia than one based on a single assessment of school performance and cognitive functions, therefore avoiding false-positive cases and high demand clinical services diagnosis wait.